Hedonic shopping motivation on impulse buying: Evidence on Indonesian e-commerce users during Covid-19 - Putu Agus Perinanta Putra; Ni Kadek Melly Ardani; Putu Ratna Juwita Sari (Review of Management, Accounting, and Business Studies, 2024)
Consumers who like shopping, have a greater tendency to seek information about certain products. If the information obtained is about a product that can attract the heart, it will bring up the desire to have the item immediately, so that impulse buying occurs. This study also aims to find the existence of the influence of idea shopping, value shopping, and gratification shopping on impulse buying among buyers in Zalora. The sample was taken by using purposive sampling method with 100 respondents. Data collection technique was carried out using a questionnaire distributed online via Google Form. The results show partially and simultaneously Idea Shopping, Value Shopping, and Gratification Shopping has been proven to have a positive and effect on impulse buying.